Media Literacy for Herbalist in Medan City (Talenta Publisher, 2020)
The rise of hoax news circulating on social media at a certain point can cause confusion and anxiety in society. Therefore, this community service group took the initiative to carry out a media literacy activity for the herbs seller (herbalist) group of Yayasan Perempuan Perkotaan Medan (YP2M). This activity aims to facilitate the group so that they have the skills to respond to the hoax news. The materials provided include what the news is, the news values, the characteristics of hoax news, and the examples of hoax news that are widely spread in society through the social media. This program was held in Gedung Johor, Medan on August 2020 which was attended by around 20 participants. Keywords: media literacy, hoax news, YP2M